Pengaruh Stimulus Lingkungan Toko Terhadap Perilaku Pembelian Tidak Terencana Yang Dimediasi Oleh Emosi Positif - Margana, Charloan Artha; Setiawan, Putu Yudi (E-Jurnal Manajemen; Vol 3 No 9 (2014), 2014)
1024x768 ABSTRACT The purpose of this study was to determine the effect of environmental stimuli of store on the behavior of unplanned purchases mediated by positive emotions on consumer hypermarket in Denpasar. This research was conducted in the city of Denpasar, the samples taken were 140 people with purposive sampling method. Data was collected through questionnaires using a 5-point Likert scale to measure 14 indicators. The analysis technique used is multiple linear regression. These results indicate that each variable enironmental stimuli of store significant positive effect on unplanned purchasing behavior and the effect was mediated by positive emotions. This suggests that the environmental stimuli of store can affect unplanned purchasing behavior and also can affect positive emotions before. Keywords : in-store stimuli, impulse buying behavior, positive emotions. Normal 0 false false false IN X-NONE X-NONE